Brief Report: Endothelial Progenitor Cell Phenotype and Function Are Impaired in Childhood‐Onset Systemic Lupus Erythematosus. Issue 8 (28th July 2015) - Mohan, Smriti; Barsalou, Julie; Bradley, Timothy J.; Slorach, Cameron; Reynolds, John A.; Hasni, Sarfaraz; Thompson, Becky; Ng, Lawrence; Levy, Deborah; Silverman, Earl; Kaplan, Mariana J.
<x xml:space="preserve">Abstract</x> Objective Systemic lupus erythematosus (SLE) is characterized by increased cardiovascular risk in adult‐onset and childhood‐onset SLE. Type I interferons (IFNs) appear to play a prominent role in premature vascular damage in adult‐onset SLE, at least in part, by inducing impairments in the phenotype and function of endothelial progenitor cells (EPCs), thereby hampering vascular repair. It is not clear whether EPC dysfunction is present in childhood‐onset SLE in association with a type I IFN signature. Methods The phenotype and numbers of EPCs were quantified in patients with childhood‐onset SLE, patients with juvenile idiopathic arthritis (JIA), and matched healthy control subjects. In a separate cohort of patients with childhood‐onset SLE, markers of subclinical atherosclerosis and endothelial dysfunction were quantified using standardized protocols and analyzed for associations with serum type I IFN activity. Results EPC numbers and function were significantly decreased in patients with childhood‐onset SLE compared with patients with JIA and healthy control subjects. Serum from patients with childhood‐onset SLE impaired differentiation of EPCs into mature endothelial cells in healthy controls, and this effect was blocked by inhibition of the type I IFN pathway. Type I IFN activity in serum was not significantly associated with subclinical atherosclerosis and endothelial function in patients with childhood‐onset SLE. Conclusion As in adult‐onset SLE, childhood‐onset SLE is characterized by phenotypic and functional EPC abnormalities, which are likely triggered by type I IFNs. Although cross‐sectional analysis revealed no global association between type I IFN signatures and vascular measures of subclinical atherosclerosis, longitudinal assessments are needed to evaluate whether progression of vascular damage in patients with childhood‐onset SLE is associated with type I IFNs, as observed in patients with adult‐onset SLE.